Mastomys natalensis (Smith, 1834) as a natural host for Schistosoma haematobium (Bilharz, 1852) Weinland, 1858 x Schistosoma bovis Sonsino, 1876 introgressive hybrids - Savassi, Boris A.E.S.; Dobigny, Gauthier, G.; Etougbétché, Jonas; Avocegan, Thalasse, T; Quinsou, François, T; Gauthier, Philippe; Ibikounlé, Moudachirou; Moné, Hélène; Mouahid, Gabriel (Tropical Medicine and Infectious Disease, 2021)
Sequence data were deposited in the NCBI GenBank database under the accession numbers MW022134 to MW022147 for COI mtDNA and MW027648 to MW027658 for ITS rDNA. International audience Cercarial emission of schistosomes is a determinant in the transmission to the definitive host and constitutes a good marker to identify which definitive host is responsible for transmission, mainly in introgressive hybridization situations. Our goal was to test the hypothesis that micromammals play a role in Schistosoma haematobium, S. bovis, and/or S. haematobium x S. bovis transmission. Small mammal sampling was conducted in seven semi-lacustrine villages of southern Benin. Among the 62 animals trapped, 50 individuals were investigated for Schistosoma adults and eggs: 37 Rattus rattus, 3 Rattus norvegicus, 9 Mastomys natalensis, and 1 Crocidura olivieri. Schistosoma adults were found in four R. rattus and two M. natalensis, with a local prevalence reaching 80% and 50%, respectively. Two cercarial chronotypes were found from Bulinus globosus experimentally infected with miracidia extracted from naturally infected M. natalensis: a late diurnal and nocturnal chronotype, and an early diurnal, late diurnal, and nocturnal chronotype. The cytochrome C oxidase subunit I mtDNA gene of the collected schistosomes (adults, miracidia, and cercariae) belonged to the S. bovis clade. Eleven internal transcribed spacer rDNA profiles were found; four belonged to S. bovis and seven to S. haematobium x S. bovis. These molecular results together with the observed multi-peak chronotypes add M. natalensis as a new host implicated in S. haematobium x S. bovis transmission. We discuss the origin of the new chronotypes which have become more complex with the appearance of several peaks in a 24-h day. We also discuss how the new populations of offspring may optimize intra-host ecological niche, host spectrum, and transmission time period.